Human Development Index (HDI) in Lampung Province Period 2013-2018 - Ambya Ambya (Faculty of Economics, Universitas Sriwijaya, 2020)
Human development index (HDI) is one of the benchmarks used to see the quality of human life as measured by looking at the level of human life quality of education, health and economy. This study aims to determine the effect of government spending from the education, health expenditure, capital expenditure sectors and lastly income per capita on the human development index. The data used is a secondary data in 7 districts in Lampung Province period of 2013-2018 which uses the secondary data in the form of panel data, which is a combination of time series and data obtained cross section. The analysis shows that government spending in the health sector, education, capital expenditure and gross regional product growth has a positive and significant effect on the human development index. Together the independent variables can increase the human development index close to seventy percent.